COMPUTER NETWORK ANALYSIS USING NETWORK MANAGEMENT SYSTEM AT AN NUUR UNIVERSITY - Achmad Rizki Ramadhani; Muhammad Akbar Mustofa; Rahmawan Bagus Trianto (Julia: Jurnal Ilmu Komputer An Nuur, 2021)
During the pandemic, teaching and learning activities have changed. Which originally used the offline format to go online and its combinations. Internet bandwidth usage plays an important role in the success of the teaching and learning process on campus, including at An Nuur University. By using Cacti Network Management System it can be used as a monitoring system to monitor the movement of internet bandwidth whether it meets the needs of the online learning process or not. Internet bandwidth usage is influenced by several factors such as logical topology, physical topology and configuration in computer networks.